The Oral Microbiome Profile of Water Polo Players Aged 16–20 - Irina Kalabiska; Dorina Annar; Zsuzsa Keki; Zoltan Borbas; Harjit Pal Bhattoa; Annamaria Zsakai (Sports, 2023)
Objectives: Chlorine has a strong antibacterial property and is the disinfectant most frequently used in swimming pools. Therefore, the microbiota community in the oral cavity of those who practice water sports is assumed to be special due to their regular immersion in water. Adverse changes in the composition of oral cavity microbiota may have serious health consequences. We aimed to compare the oral microbiome between water polo players and non-athletes. We hypothesized that the oral cavity microbiota community differed between water polo players and non-athletes. Materials and Methods: Altogether, 124 water polo players (62 males and 62 females, aged between 9 and 20 years) and 16 non-athlete youths (control group, eight males and eight females, aged between 16 and 20 years, mean age + SD = 17.1 + 1.4 years) who participated in body structure examinations voluntarily agreed to participate in the study. In a randomly selected subsample of water polo players (n: 29, aged between 16 and 20 years, mean age + SD = 17.3 + 1.0 years), saliva samples were also collected. Saliva samples were collected from all non-athlete youths (n: 16, aged between 16 and 20 years). The oral microbiome was determined from a saliva sample, and DNA was isolated using the QIAmp DNA Blood Mini Kit. The 16S rRNA gene amplicon sequencing method was used to analyze the microbiome community. PCR primers were trimmed from the sequence reads with Cutadapt. R library DADA2 was used to process reads in the abundance analysis. Results: In general, Streptococcus, Veilonella, and Prevotella genera constituted more than 50% of the oral microbiome community in the two participant groups combined (n = 45). The oral microbial profile had significant sexual dimorphism and differed between water polo players and the non-athletes. Compared to females, males had a higher (p < 0.05) relative abundance of the Atopobium (medium effect size) and Pravotella_7 (very large effect size) genera and a lower (p < 0.05) relative abundance of the Fusobacterium (large effect size), Gemella (large effect size), and Streptococcus (large effect size) genera. Compared to non-athletes, water polo players had higher (p < 0.05, medium effect size) relative abundance of the genus Veillonella and lower (p < 0.05, large effect size) relative abundance of the genus Gemella. Conclusions: The results suggest that regular water training can unfavorably alter the composition of the oral microbial community.